Role of PLA2R domain antibodies and epitope spreading in risk stratification and prediction of proteinuria remission in primary membranous nephropathy - Xiran Zhang; Feiya Yang; Yun Fan; Jing Xue; Bin Liu; Zhijian Zhang; Weiwei Shan; Hanzhi Chen; Ting Cai; Leting Zhou; Biao Huang; Liang Wang; et al. (Scientific Reports)
Abstract The clinical significance of phospholipase A2 receptor (PLA2R) antigen domain-specific antibodies has not been determined. We investigated the role of serum PLA2R domain antibodies and epitope spreading in risk stratification and proteinuria remission in primary membranous nephropathy (PMN). Overall, 101 patients with PLA2R-associated MN diagnosed at the Wuxi People’s Hospital between January 2019 and May 2021 were included and divided into low-to-medium risk (n = 12) and high-to-extremely-high risk (n = 89) groups. Serum PLA2R-IgG4 levels were significantly different between the groups, no statistical difference was found in PLA2R-IgG levels. The proportion of IgG4 epitope spreading was greater in the high-to-extremely-high risk group than in the low-to-medium risk group. The result of random forest machine learning method showed that combining the three variables (PLA2R-CTLD678-IgG4, PLA2R-CysR-IgG4, and IgG4 epitope-spreading) showed no significant difference in PMN risk stratification than that of PLA2R-IgG. For predicting proteinuria at 12 months, the ACC values were significantly greater for PLA2R-CTLD1-IgG4, PLA2R-CTLD678-IgG4, and PLA2R-IgG4 than for PLA2R-IgG. Combining IgG4 epitope-spreading and PLA2R-IgG may improve the ACC value of proteinuria prediction after 6 months of treatment compared with PLA2R-IgG alone. PLA2R-CTLD1-IgG4, PLA2R-CTLD678-IgG4, and PLA2R-IgG4 can predict proteinuria remission more accurately at 12 months of treatment than PLA2R-IgG.